Entrepreneurship Orientation And Business Innovation Towards Creative Economy Based SMEs Performance In Makassar City - Naidah Naidah; Asdar; Muhammad Rusydi; Syarifuddin Sulaeman (Yayasan Riset dan Pengembangan Intelektual, 2023)
Problems regarding the performance of SMEs based on the creative economy have become a priority issue for both practitioners and academics. This research is important not only because it complies with the specifications of PTMA Basic Research (PD PTMA) but also because research related to the performance of SMEs based on creative economy tends to experience complex challenges and problems. The purpose of this study was to analyze the level of influence of entrepreneurial orientation on the performance of creative economy-based SMEs through the mediation of business innovation variables. This study uses a quantitative approach to examine the direct and indirect effects of structural equation modeling analysis techniques. The phasing method is carried out as follows: (1) identify the level of influence of entrepreneurial orientation on the performance of SMEs based on the creative economy; (2) analyze the level of influence of business innovation variables on the performance of creative economy-based SMEs; (3) examine the level of influence of business innovation variables in mediating entrepreneurial orientation variables on the performance of creative economy-based SMEs to generate practical and theoretical contributions. The results of this study indicate that entrepreneurial orientation has a positive relationship with business innovation, entrepreneurial orientation also has a positive influence on SME performance, business innovation is proven to have a positive influence on SME performance, business innovation can be a mediating variable between entrepreneurial orientation and SME performance.